(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To review of clinical characteristics of pregnant women undergoing laparoscopic surgery for ovarian tumors at Hanoi Obstetrics and Gynecology Hospital. Material and methods: A cross-sectional retrospective study of over 74 pregnant women diagnosed with ovarian tumors who underwent laparoscopic surgical intervention at Hanoi Obstetrics and Gynecology Hospital from January 1, 2019 to December 31, 2023. Results: The average age of pregnant women diagnosed with ovarian tumors in the study was 27.1 ± 4.0, often found in employees. The most common complaint of patients admitted to the hospital is pain in the lower abdomen with 74.3%. Most patients have 1 child (32.4%) and have old abdominal surgery (35.2%). The most common gestational age when detected is ≤ 12 weeks of age with a rate of 79.7% and up to 67.6% of pregnant women require surgery during pregnancy at this age. The duration of abdominal pain in pregnant women is less than 24 hours, accounting for the largest proportion with 43.2%. Conclusions: Our research results show that the 20-35 age group is the most common group. At this age, many people have not given birth to enough children, so preserving the ovaries during surgery is an important factor to ensure fertility. For young patients who do not have enough children, choosing laparoscopic surgery is an optimal solution to both treat the disease and maintain fertility. Laparoscopic surgery in patients with old abdominal incisions is no longer a strict contraindication, and laparoscopic techniques have become safer and more effective. However, caution is still needed when prescribing laparoscopic surgery for these cases.